Overview of Health Paradiplomacy: A Bibliographic Study - Siti Nurindah Mointi; Destian K Rauf; Moh. Falmes Lakadjo; Adnan Malaha (Journal of Governance and Global Studies, 2025)
This bibliographic study aims to identify trends, actors, themes, and patterns of cooperation in the literature and practice of Indonesian health paradiplomacy from 2020 to 2025. The method used is a qualitative approach with descriptive-analytical methods and content analysis techniques on 13 relevant articles from online searches. The results show a steady increase in health paradiplomacy practices and studies during this period, with Japan as the dominant partner and regional mayors as the most active local actors. The findings of the content analysis (word frequency query) show that the main focus is on improving public services (25.74%), the role of regions (11.24%), and cooperation through schemes such as sister cities. The main conclusion is that health paradiplomacy is growing rapidly, focusing on improving public services and strengthening regional capacity through international collaboration. Recommendations include the need to strengthen the documentation of cooperation databases, increase the capacity of human resources in health diplomacy, and support academic research. The implications of this research are as a scientific database for policy makers in strengthening central-regional synergies for an inclusive and sustainable national health system resilience.